A short, offhand, killing affair : soldiers and social conflict during the Mexican-American War - Foos, Paul, 1959- (University of North Carolina Press, 2002)
The Mexican-American War found Americans on new terrain. A republic founded on the principle of defending freedom was now going to war on behalf of maifest destiny to conquer another nation. Through primary accounts of the soldiers and the war, Foos examines its effect on America.